2021
DOI: 10.21468/scipostphys.11.6.105
|View full text |Cite
|
Sign up to set email alerts
|

Generalized eigenproblem without fermion doubling for Dirac fermions on a lattice

Abstract: The spatial discretization of the single-cone Dirac Hamiltonian on the surface of a topological insulator or superconductor needs a special ``staggered’’ grid, to avoid the appearance of a spurious second cone in the Brillouin zone. We adapt the Stacey discretization from lattice gauge theory to produce a generalized eigenvalue problem, of the form \bm{\mathcal H}\bm{\psi}=\bm{E}\bm{\mathcal P}\bm{\psi}ℋ𝛙=𝐄𝒫𝛙, with Hermitian tight-binding operators \bm{\mathcal H}ℋ, \bm{\mathcal P}𝒫, a locally conserved p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…TMDCs are semiconducting 2D crystals, such as WSe 2 or MoS 2 , with strong spin-orbit. The possibility of inducing a strong SOC on graphene monolayers by placing it in contact to a TMDC was demonstrated using a variety of theoretical [66][67][68] and experimental techniques [55][56][57][57][58][59][60]. Two main types of SOC are generated on the low-energy sector of monolayer graphene close to the neutrality point: Ising and Rashba [59,60,67].…”
Section: Introductionmentioning
confidence: 99%
“…TMDCs are semiconducting 2D crystals, such as WSe 2 or MoS 2 , with strong spin-orbit. The possibility of inducing a strong SOC on graphene monolayers by placing it in contact to a TMDC was demonstrated using a variety of theoretical [66][67][68] and experimental techniques [55][56][57][57][58][59][60]. Two main types of SOC are generated on the low-energy sector of monolayer graphene close to the neutrality point: Ising and Rashba [59,60,67].…”
Section: Introductionmentioning
confidence: 99%
“…Over the years, various remedies have been put forward that can be clustered into two general categories according to the dimensionality of the underlying model. The first category contains true two-dimensional models, such as Wilson fermions [2,3] or staggered fermions [4][5][6]. These are computationally efficient but complicate the description and bandstructure of the system.…”
Section: Introductionmentioning
confidence: 99%
“…[13] (at the level of the scattering matrix) and in ref. [14] (at the level of the Hamiltonian). It was shown that the eigenvalue equation HnormalΨ=EnormalΨ$H\Psi =E\Psi$ can be discretized into a generalized eigenvalue problem scriptHnormalΨ=EscriptPnormalΨ${\cal H}\Psi =E{\cal P}\Psi$ with local Hermitian tight‐binding operators on both sides of the equation.…”
Section: Introductionmentioning
confidence: 99%
“…In what follows we turn to the dynamical problem, by generalizing the approach of refs. [12–14] to the discretization of space and time. In the next Section 2 we show that the time discretization removes the pole in the tangent dispersion, which becomes a smooth function of momentum k$\bm {k}$ and quasi‐energy ε (yellow bands in Figure 1).…”
Section: Introductionmentioning
confidence: 99%